2019
DOI: 10.1097/md.0000000000016704
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of human leukocyte antigen allele polymorphism in patients with non alcoholic fatty liver disease

Abstract: The human leukocyte antigen (HLA) genes may play a role in the pathogenesis of non-alcoholic fatty liver disease (NAFLD) and its progressive form, non-alcoholic steatohepatitis (NASH). The aim of this study was to assess the association of HLA class I and II alleles with NASH and its histological features. Deoxyribonucleic acid (DNA) was extracted from 140 subjects (85 biopsy-proven NAFLD and 55 controls) and genotyped for HLA (-A, -B, -C, -DR1, -DR3, -DQ, and -DP). Liver biopsies were assessed for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 32 publications
(29 reference statements)
0
8
0
Order By: Relevance
“…To clarify how it affects the pathogenesis of NAFLD, we evaluated the association between the B*54:01 allele and microbiome. Some reports have shown that particular HLA alleles are associated with NAFLD, (41,42) but we have no knowledge about the pathogenic roles of HLA alleles in NAFLD development. One possibility is HLA affects liver injury through the immune system directly, and another is that HLA might regulate NAFLD indirectly through the microbiome.…”
Section: Discussionmentioning
confidence: 97%
“…To clarify how it affects the pathogenesis of NAFLD, we evaluated the association between the B*54:01 allele and microbiome. Some reports have shown that particular HLA alleles are associated with NAFLD, (41,42) but we have no knowledge about the pathogenic roles of HLA alleles in NAFLD development. One possibility is HLA affects liver injury through the immune system directly, and another is that HLA might regulate NAFLD indirectly through the microbiome.…”
Section: Discussionmentioning
confidence: 97%
“…24 In a study of 85 adults with biopsy-proven NAFLD, investigators performed genetic testing to explore associations between HLA haplotypes and disease severity. 25…”
Section: Discussionmentioning
confidence: 99%
“…The majority of pediatric AIH is associated with HLA‐DRB1*0301 24 . In a study of 85 adults with biopsy‐proven NAFLD, investigators performed genetic testing to explore associations between HLA haplotypes and disease severity 25 . HLA‐DRB1*03 was associated with an increased risk of NASH, while HLA‐B*27 was associated with severe steatosis.…”
Section: Discussionmentioning
confidence: 99%
“…The genetic connection between the variables in the pathogenesis of NAFLD and NASH developments has been concerned (Karrar et al, 2019). Earlier studies showed that NAFLD could exist in the nonobese subjects of 10-20%, most frequently associated with central adiposity, recent weight gain, and genetic risk factors (Namjou et al, 2019).…”
Section: Introductionmentioning
confidence: 99%